Gain improvement in L-band EDFA using unpumped EDF in a double pass system - Harun, Sulaiman Wadi; Tamchek, Nizam; Poopalan, Prabakaran; Ahmad, Harith (John Wiley & Sons, 2003)
A new gain improvement technique for L-band EDFA is presented. It uses an unpumped EDF in a double-pass configuration in order to effectively suppress and completely exploit the backward ASE. Compared to a conventional single-pass amplifier, the gain coefficient can be improved from 1.5 dB/mW to 3.1 dB/mW without much noise figure penalty. The L-band EDFA can also reduce the pump power necessary to achieve a specified gain by about half, however, this occurs at the cost of noise figure increasing by 1.6 dB. The optimum length for an unpumped EDF is experimentally measured to be 3 m for both single-pass and double-pass systems. The maximum gain improvement of 15.5 dB was observed at a signal wavelength of 1572 nm while signal and pump powers were fixed at - 30 dBm and 103 mW, respectively.